From text to e-text: perceptions of medical, dental and allied students about e-learning - Ayesha Fahim (15231868) (2022)
Objective More than a year ago, Pakistan like the rest of the word, was hit by a global pandemic, due to which students of higher education had to accept the new era and adapt to the electronic learning environment for the very first time. This study aims to analyze the perceptions of medical, dental, and allied health students about e-learning in Pakistan. Methods A descriptive, cross-sectional study was conducted throughout the country. A pre-validated, anonymous online questionnaire regarding demographics, past-experience of e-learning, advantages disadvantages of e-learning, and general perception of students towards e-learning was distributed. Descriptive statistics were computed for all demographics. Chi-square test was used to compare the differences of perceptions between pre-clinical year and clinical years students. Chi-square was used to compare overall category-wise positive and negative responses of students. The association between participant demographics and their perception towards e-learning was also calculated using chi square. Results A total of 1200 students participated in the study of which 797 (66.4%) were from pre-clinical years and 403 (33.6%) were from clinical years. The major advantage identified by all students was the ‘comfortable environment’ (70%) and ‘technical problems with IT equipment’ was listed as the biggest disadvantage (89%) of e-learning. For preclinical year students, ‘anxiety due to social isolation’ was selected as the biggest issue (p < 0.05) whereas, for clinical year students, it was ‘lack of patient interaction’ (p < 0.05). Overall, 72% of students had a negative perception of e-learning. Conclusion After more than a year of online studying, medical and allied students of Pakistan have expressed dissatisfaction towards e-learning. Student-teacher training, student counselling sessions, and innovative techniques need to be introduced to enhance student engagement and reduce pandemic stress. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2022.e12157